Empirical Study on Shopper’s Satisfaction and Retailers Service Quality in Muscat Governorate, Oman: Using SERVQUAL model - et. al., Mathew Philip, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
People of the Sultanate of Oman rely on retail hypermarkets to fulfill their basic needs including food products. To retain the customers’ loyalty and to retain the customers, it is important to satisfy the customers. The retail and hypermarkets focus on finding out and measuring the elements to offer the customers with good quality products and services. The objective of this study is to use the SERVQUAL model to understand the significance of various elements of customer satisfaction and how to accomplish the expected customer satisfaction by improving the services in Muscat. To achieve the objectives, the questionnaire was floated online and data was collected from the customers who visit the hypermarkets. The collected data was analyzed and the findings of the study show that the hypermarkets are delivering services of high quality which enabled the hypermarkets to keep customers as loyal with higher satisfaction. Regardless of this, the study found out that there is still room for progress in terms of improving the handling of customers by the employees to avoid the adverse effect on the hypermarkets’ revenue and operations.